Human Resource Competency Development as an Environmentally Friendly Entrepreneurship Strategy in MSME Cafés in Ermera, Timor-Leste (A Conceptual Study) - Casimiro Soares; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Greenation Research & Yayasan Global Resarch National, 2025)
This article aims to analyze human resource (HR) competency development as a strategy for realizing environmentally friendly entrepreneurship in MSME cafés in Ermera Regency, Timor-Leste. This study is conceptual in nature, examining various theories and current empirical findings related to HR competency, sustainable entrepreneurship, and environmentally friendly business practices in the MSME sector. HR competency development is seen as an important foundation for MSMEs in adopting green entrepreneurial behavior, including innovation capabilities, environmental knowledge, sustainable attitudes, and managerial skills that support resource efficiency. This study found that structured HR competency can encourage the emergence of environmentally friendly entrepreneurial strategies, such as waste reduction, efficient energy use, environmentally friendly product innovation, and strengthening the image of green businesses. Through conceptual analysis and theoretical integration, this article offers a conceptual model that explains the relationship between HR competency development and environmentally friendly entrepreneurial strategies in the context of MSME cafés. Theoretically, this study enriches the literature related to green entrepreneurship, while practically, it provides an overview for MSMEs, local governments, and supporting institutions to design HR development programs that are more oriented towards sustainability.